Becoming a Da'wah Artist: Evaluation of the Live in Da'wah Program to Improve Student Morale with the CIPP Model - Heni Nadia Fitriana; Suwadi Suwadi (Universitas Muhammadiyah Enrekang, 2024)
Penelitian ini difokuskan pada evaluasi program